Grundtvigs skovoplevelse i 1811 og prædikerne over Peters fiskedræt i tiden, der fulgte - Thodberg, Christian (Grundtvig-studier, 1986)
Grundtvig’s Experience in a Wood in 1811 and his subsequent sermons on the miraculous draught of fishes.By Christian Thodberg.It is common knowledge that in connection with the revival of his Christianity Grundtvig suffered a breakdown in December 1810, after which he returned with his friend, F. C. Sibbern, to his home village and his parents in Udby, South Zealand. However, in May 1811, after a stay in Copenhagen, he was again on his way to Udby to become curate for his aging father when he had an equally important experience in the wood outside Udby which has hitherto passed apparently unheeded. He describes it in a contemporary poem to Sibbern himself.In an attack of despondency, brought on by the sight of Udby church and his childhood home and by the thought of his forthcoming ministry, he knelt down in the wood and read I Cor. 15: 55-58. Grundtvig had been ordained in Copenhagen on May 29th, but in the wood two days later he experienced a special call to the priesthood. The nature of this experience is clearly visible in his sermon for the 5th Sunday after Trinity on the miraculous draught of fishes (Luke 5: 1-11), given 22 years later on July 7th 1833. In the sermon Grundtvig relates the experience and adds that the Lord Himself had spoken to him on that occasion and had called him with the words used to Simon Peter: “ Let down the net. From henceforth thou shalt catch men!”A closer analysis of Grundtvig’s sermons from 1811 until his death in 1872 shows that over the years it is on the 5th Sunday after Trinity that he reflects on the Lord’s special call to him, and thus on his life’s special destiny. He uses Peter’s catch as his starting-point, both because of Jesus’ words to Peter and because the frightened and kneeling Peter in the gospel story undoubtedly reminds Grundtvig of his situation and literal position in the wood on Friday May 31st 1811.In his sermon for the 5th Sunday after Trinity 1811 the call motif does not appear; on the other hand he does use the biblical themes of Ezek. 47: 8-10 and Amos 8: 11, which are repeated in the later sermons on the miraculous draught. The unfinished sermon of 1812 is of a quite different order, but the very long sermon in 1818 is such a penetrating analysis of the preacher’s situation that it reveals Grundtvig’s extremely personal relationship to the account of Peter’s call. The same tension can be felt in the three drafts for the sermon of 1821; the last draft is continued in the major prose-poem sermon of 1822. The theme is “listening to God’s Word”, and the sermon is divided into five images: the first depicts the days of the ancient covenant, when the Jews refused to listen and ended up under the curse of slavery; the second is John the Baptist’s sermon; the third is Jesus’ teachings and works, while the fourth is the Church’s enthusiastic reflection on this central vision. The fifth image is basically Grundtvig’s own prophecy for the near future and for himself; for it is he himself who through his coming activity in Copenhagen, Denmark’s Jerusalem, will be the crucial link in the renewal of the salvation story. So self-conscious a sermon could not but have its source in a personal revelation, that is, the experience om May 31st 1811. The first sermon in Copenhagen in 1823 already includes the biblical themes mentioned above and describes the coming Christian revival. In the highly-charged sermon of 1824 Grundtvig clearly recalls the beginning of his ministry in 1811 and confesses that he has never preached better! This particular sermon of 1824 affords grounds for an analysis of the two central poems from that year: The Land o f the Living and N ew Year’s Morn, which were most probably written in June and July 1824 respectively. The Land o f the Living contains three sequences: 1) the childhood dream, 2) the vain dream of the adult worldling, and 3) the childhood dream recovered. The same three themes are also to be found in the poem to Sibbern, and the experience in the wood in 1811 offers a plausible explanation of the break between stanzas 1-6 and 7-13, i.e. between the description of the vain dream of the adult worldling and the childhood dream recovered. In fact it is compelling to regard stanzas 7-8 as a retelling in poetic form of the experience in the wood. The same experience would also seem to have left a significant trace in N ew Year’s Morn, in stanza 54 where there are similarities as regards both content and language between the Sibbern poem of 1811 and the retelling of the experience in the wood in the sermon of 1824.Among the reworked sermons in The Sunday Book we find in Vol. II (1828) a memoir of 1811 in a sermon on the miraculous draught of fishes, but the personal experience is emphasised by the stress, under the inspiration of Irenaeus, on the human as a prerequisite for the Christian. The gospel of the day must be particularly comforting to people torn between fear and hope – like Grundtvig in 1811. Jesus’ calling of Peter is again recalled in 1832 as the basic premise for Grundtvig’s own ministry. The sermon of 1833 - the cornerstone of this survey - has already been mentioned. In 1834 Jesus’ words to Peter are underlined with a minor gloss: fisher of living men, from which Grundtvig argues for his new view of the Church: the capacious Church. People must not be forced into Christianity, and they must be allowed to choose the priest they wish to attach themselves to. In 1835 Grundtvig recalls his ordination in 1811. In 1836 the human aspect of the sermon is emphasised, as it is in The Sunday Book.In 1837 Grundtvig uses the call of Peter to consider the justification of lay preaching - presumably because he himself received a direct call in 1811. In 1838 the Irenaeus inspiration culminates. The dangerous life of a fisherman is a precise image of the rightness of Grundtvig’s well-known thesis: First a Man, then a Christian. In 1839 the experience in the wood is retold, this time in even more detail than in 1833; while in 1840 Grundtvig demonstratively sets his two great “revelations” up against one another: the experience in the wood in 1811 and the “unparalleled discovery” of baptism and the eucharist in 1825. From now on it is clear to him that the later “revelation’ is the greater, a belief he finally confirms in his sermon of 1842. Irenaeus continues to inspire him in the sermons of 1841 and 1844, underlining yet again Grundtvig’s personal relationship to the account of the miraculous draught. In the remainder of Grundtvig’s preaching life the, experience of 1811 is less strongly recalled on the 5th Sunday after Trinity, though it does happen both in 1856 and in 1861.The survey shows that the experience has been of central significance to the revival of Grundtvig’s faith, and that right into the 1840s it is an important starting-point for his understanding of himself as a Christian. The sermon on the 5th Sunday after Trinity on the miraculous draught of fishes thus becomes an interesting guideline to an appreciation of Grundtvig’s personal and theological development.